Toys in space - Grey, Mini. (New York : Alfred A. Knopf, 2012)
A group of toys, left out at night for the first time, begin to be afraid, but the WonderDoll distracts them by weaving a story of lost toys, space travel, and a strange alien.
Kirkus Review
Pub Weekly
Kirkus Review, April 2013
Pub Weekly, March 2013
2.3
K-3.
Keywords: Night -- Juvenile fiction; Storytelling -- Juvenile fiction; Toys -- Juvenile fiction; Night -- Fiction; Storytelling -- Fiction; Toys -- Fiction; Night -- Fiction; Storytelling -- Fiction; Toys -- Fiction; Picture books for children